Gráfico de controle da média móvel exponencialmente ponderada: Aplicação na operação e monitoramento de uma estação de tratamento de esgoto - Orssatto, Fábio; Boas, Marcio Vilas [UNESP]; Eyng, Eduardo (My University, 2015)
This work was intended to assess the performance of a sewage treatment plant through letters of statistical quality control of exponentially weighted moving average. The sewage treatment plant is located in the municipality studied of Cascavel, Paraná, the parameters measured were the hydrogenionic potential (pH), settleable solids (SetS), total suspended solids (TSS), chemical oxygen demand (COD), biochemical oxygen demand (BOD). The EWMA letters accused that sewage treatment station has good statistical performance for the pH, total suspended solids, COD and BOD and failures for settleable solids. The EWMA control letters are presented as a good alternative in monitoring of sewage treatment plants.
Exponentially weighted moving average control chart: Application in the operation and monitoring of a sewage treatment plant
Keywords: Exponentially Weighted Moving Average; Process control; Sewage treatment